Autocuidado del adulto mayor para un envejecimiento con bienestar y su relación con inpendencia funcional y estado cognitivo - Meléndez Vilchez, Teresa de Jesús (2014)
This research work is a quantitative descriptive correlational study, which is crosssectional. This study was conducted during the months of January, February to March 2014, performed in the Senior's adult Programme of the Es Salud Hospital, AlbrechtTrujillo. In this study, 100 old adults over 60 years from both sexes participated who complied with inclusion's standarts, three Scale of assessment were used for: the first one was a Self-Care scale to live an old age with welfare, the second one was a Scale of Cognitive Status and the last one was a Functional Independence assessment scale.After carrying out this research work, the following inferences were gotten: Analysis and discussion of the results reached the following conclusions 1.-The majority self-care of seniors is good . 2.-The majority In the basic activities of daily living,e instrumental activities of 99% of older adults have a functional level of independence which is moderately independent. 3.-The majority old adults have an average cognitive status ,the cognitive's status level of 12% of old adults is mild cognitive impairment(MCI), and 1% of seniors have a moderate pathological impairment cognitive in their cognitive status. 4.-The level of functional independence their basic activities of daily living is moderately independent and their self-care level is great adults in their basic activities and in their instrumental activities of daily living is independent witha chi-square value of 4.602 with probability 0.032 is seen with a level of significance, this is why there is a relationship between variables. 5.Also ,the cognitive status. Additionally, a value of 4.238 Chi-square with probability 0.039 is observed to be significant, so it means there is a relation between the mentioned variables.